Embedded System Technology 13th National Conference, ESTC 2015, Beijing, China, October 10-11, 2015, Revised Selected Papers - Zhang, Xing; Wu, Zhonghai; Sha, Xingmian (Communications in Computer and Information Science, 2015)
This book constitutes the refereed proceedings of the 13th National Conference on Embedded System Technology, ESTC 2015, held in Beijing, China, in October 2015. The 18 revised full papers presented were carefully reviewed and selected from 63 papers. The topics cover a broad range of fields focusing on research about embedded system technologies, such as smart hardware, system and network, applications and algorithm.